CHEMISORPTIVE EMISSION AND LUMINESCENCE .1. CHLORINE-ZIRCONIUM - Prince, R; Lambert, R; Foord, J (1981)
Experimental data for electron and photon emissions during the chemisorption of chlorine on pure and sodium-doped zirconium are presented, and a quantitative model is given which adequately describes the gross features of the electron emission process. The model is based on invoking a tunnelling mechanism and relaxation by a radiationless (Auger) process, and draws heavily on previous successful theories for Auger ion neutralization to predict the energy distribution functions for subsequent emissions. For a high electron affinity species such as chlorine, the observed chemisorptive emission yields are strongly dependent on work function varying from 10-6 to 10-2 electrons per incident atom, and following a cubic dependence on the excess energy available. Chemisorptive luminescence is also observed, at levels of ~10-8 photons per incident atom in accordance with previous estimates. A self-consistent kinetic analysis is presented to describe the rapid decay of these emission processes following the onset of chemisorption. © 1981.